Three dimensional structure of AFLR2 produced from Aspergillus parasiticus (World Journal of Experimental Biosciences, 2015)
Present study focused on the structure of Aflatoxin B1 Regulatory Gene that was isolated from environmental Aspergillus parasiticus isolate. After purification of the studied Aflatoxins are polyketide derived secondary metabolites produced by A. parasiticus spp. The toxic effects of aflatoxins are adverse consequences on human health and agricultural economics. The aflR2 gene is regulatory gene for aflatoxin biosynthesis encodes a protein containing a zinc-finger DNA-binding motif. AFLR-Protein three-dimensional model was generated using Robetta server. The modeled AFLR-Protein was further optimization and validation using Rampage. In the simulations, we monitored the backbone atoms and the C-α-helix of the modeled protein.